School's out, learning's in : home-learning activities to keep children engaged, curious, and thoughtful - Nottingham, Jill; Bergmann, Carmen, 1972-; Nottingham, James (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book is an accessible guide to helping boost your child's language, curiosity, and problem-solving abilities outside of the classroom. Packed full of learning activities for children and teaching advice for parents, this book is specifically designed to support parents engaging your children in thought-provoking conversations and problem-solving strategies. Divided into two parts, the authors first guide readers through "Learning Pit" theory, then present a range of lesson suggestions and useful resources for parents to draw on. This book will give you: Ideas for learning with friends and family, Tools to ensure your children make the most of the feedback, Resource cards and practical suggestions with each activity, Confidence in your ability to impact your child's learning The perfect resource for parents supporting learning outside of school, School's Out, Learning's In will help you to boost your child's language, curiosity, and problem-solving abilities"--
Keywords: Learning; Activity programs in education; Problem solving in children; Thought and thinking -- Study and teaching (Elementary); EDUCATION / General; Home-learning activities